2017
DOI: 10.1039/c7ra11771j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of copolyesters with bio-based lauric diacid: structure and physico-mechanical studies

Abstract: Copolyesters developed from bio-based long-chain dicarboxylic acid show promising mechanical properties that are helpful for their application as biodegradable materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…It can be found that two narrow and sharp diffraction peaks located at 2θ = 21.5 • and 24.2 • appeared in the pattern, representing the typical (110) and (200) planes of the orthorhombic unit cell, which are consistent with the results reported in the literature [26]. The peak positions of PBD and PE are almost the same [27,28], suggesting they have similar crystal structures. The same diffraction pattern of the PBD and the branched PBD meant that the branching did not change the crystal structure of the PBD.…”
Section: The Chemical Structures and Compositionssupporting
confidence: 88%
“…It can be found that two narrow and sharp diffraction peaks located at 2θ = 21.5 • and 24.2 • appeared in the pattern, representing the typical (110) and (200) planes of the orthorhombic unit cell, which are consistent with the results reported in the literature [26]. The peak positions of PBD and PE are almost the same [27,28], suggesting they have similar crystal structures. The same diffraction pattern of the PBD and the branched PBD meant that the branching did not change the crystal structure of the PBD.…”
Section: The Chemical Structures and Compositionssupporting
confidence: 88%
“…The WAXD diffraction pattern was used to further analyze the crystalline properties of PBD x PU y and the results are shown in Figure 8. Two distinct peaks with 2θ values at 21.22 • and 23.56 • can be observed for PBD 80% PU 20% and PBD 70% PU 30% , which are almost identical to the diffraction peaks of PBD as previously reported in the literature (2θ = 21.39 • and 23.72 • ) [37]. This suggests that the polyester soft segment in the polymer is highly crystallized.…”
Section: Crystallization Properties Of Pbd X Pu Y Filmssupporting
confidence: 84%
“…To further analyze the crystallinity of PBD x PU y , the WAXD peaks of PBD x PU y were differentiated and fitted using Peak Fit v4.12 software. The peaks of WAXD spectra of all four samples can be divided into four Gaussian-fitted peaks (21.39 • , 23.72 • , 20.60 • , 22.70 • ) according to the literature [5,37], as shown in Figure 9. The maximum fitting error was less than 0.5% and the correlation coefficient was all greater than 0.995.…”
Section: Crystallization Properties Of Pbd X Pu Y Filmsmentioning
confidence: 99%
“…[140] However,d ue to the higher amount of side reactions and yellowing generated by titanium [136] compounds, most commerciallya vailables emiaromatic polyesters are produced by using antimony and germanium oxides or am ixture of metals. Typical metals for these catalysts are tin(II), antimony(III), bismuth(III),t itanium(IV), zirconium(IV), and hafnium(IV).…”
Section: Transition-metala Lkoxidesmentioning
confidence: 99%